PENGARUH KEPEMIMPINAN DAN KEMAMPUAN MANAJERIAL TERHADAP KOMITMEN ORGANISASI PADA BANK BNI KANTOR CABANG SERANG BANTEN - Yumhi Yumhi; Okto Syafria Deddy (Universitas La Tansa Mashiro, 2020)
The level of commitment, both the company's commitment to employees, and between employees to the company is needed, because through these commitments a professional working climate will be created. This study uses a quantitative associative survey research method using regression analysis techniques. The population taken is employees with the status of having worked for more than three years without including employees of contract labor and voluntary labor. The population taken is 92 of the total number of existing employees as many as 162 employees. From the results of calculations using the formula above obtained a sample of 75 employees of Bank BNI Serang-Banten Branch Office. Based on the results of statistical calculations and data analysis that have been described in the previous chapter, it can be concluded that, there is an influence between leadership on organizational commitment. An increase in leadership will increase organizational commitment. There is an influence between managerial ability on organizational commitment. Increasing managerial abilities will increase organizational commitment. There is an influence between leadership and managerial abilities on organizational commitment. An increase in leadership and managerial abilities will increase organizational commitment.